Performance of Zinc-Difattyalkyldithyocarbamate as Anti-Friction/Anti-Wear Lubricant Additives - Komar Sutriah; Zainal Alim Mas’ud; Tun Tedja Irawadi; Mohammad Khotib (Universitas Gadjah Mada, 2014)
Dithyocarbamate is an organosulphur compound that has long been known and widely applied in various fields, including in agriculture and industry. Several variants of synthesized vegetable oil-based Zinc-difattyalkyldithyocarbamate were tested its anti-friction/anti-wear performance on four ball machine using the method of ASTM-D2783. Anti-friction/anti-wear test to six of additive variants of Zinc-difattyalkyldithyocarbamate at doses of 1.2% indicated that all variants of the product has welding point value higher than the lube base oil lubricant HVI 60, and from US Steel 136 standard for Hydraulic lubricants, but only two additive variants of Zinc-bis(lauryl palmityl)dithyocarbamate and Zinc-bis(lauryl oleyl)dithyocarbamate which has a larger load wear index value than the standard, and meet the criteria as an additive extreme pressure according to US steel 136 standard. Zinc-bis(lauryl palmityl)dithyocarbamate is an additive variant with the best performance, meet bi-functional lubricant additives criteria, as anti-friction/anti-wear and antioxidant additive.